The role of contingency and correlation in the Stroop task. Issue 10 (October 2021) - Hasshim, Nabil; Parris, Benjamin A
Facilitation (faster responses to Congruent trials compared with Neutral trials) in the Stroop task has been a difficult effect for models of cognitive control to explain. The current research investigated the role of word-response contingency, word-colour correlation, and proportion congruency in producing Stroop effects. Contingency and correlation refers to the probability of specific word-response and word-colour pairings that are implicitly learnt while performing the task. Pairs that have a higher probability of occurring are responded to faster, a finding that challenges top-down attention control accounts of Stroop task performance. However, studies that try to experimentally control for contingency and correlation typically do so by increasing the proportion of incongruent trials in the task, which cognitive control accounts posit affects interference control via the top-down biasing of attention. The present research focused on whether facilitation is also affected by contingency and correlation while additionally looking at the effect of proportion congruency. This was done in two experiments that compared the typical design of Stroop task experiments (i.e., having equal proportions of Congruent and Incongruent trials but also contingency and correlational biases) to: (a) a design that had unequal congruency proportions but no contingency or correlation bias (Experiment 1) and (b) a design where the correlation is biased but proportion congruency and contingency were not (Experiment 2). Results did not support the hypotheses that contingency or correlation affected facilitation. However, interference was almost halved in the alternative design of Experiment 2, demonstrating an effect of contingency learning in typical measures of Stroop interference.